Adolescents and aids: factors influencingy the intention to use contraceptives - Oliveira, Simone H.S.; Dias, Mardonio R.; Silva, Maria I.T. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the level of contamination of individuals by the HIV has been present for over two decades, disrespecting boards, economies and cul-tures, requiring studies in social sciences and health areas, in which we can see the search for the identification of factors that may influence on pre-ventive behaviors. Objective: identify the factors that may influence on the Behavioral Intention, on one side, of male adolescents to use condomand, in other side, of female teenagers to ask their partner for use it during the sexual intercourse. Methods: descriptive-exploratory study, of quantitative type, based on the Rational Action Theory to analyze the mentioned behaviors. It was used a sample formed by 231 adolescents who study in aprivate teaching institute in João Pessoa. Result: it was shown the significant correlations between the behavioral intention to use the condom and the attitudinal and normative components, however, only the attitude and subjective norm contributed significantly to explain the variance of the intention to adopt such behavior. In relation to the behavioral intention of asking the partner to use a condom, the correlations were significant with the subjective norm, attitude and normative belief; nonetheless, only the subjective norm explained the variance of the intention to adopt this behavior. Conclusion:the adopted theoretical reference showed different factors influencing each one o the studied behaviors, pointing possible ways of planning programs which aim to stimulate the use of condom among adolescents.